El From EFL to ELF: In the Need to Incorporate Principles of English as a Lingua Franca in Colombian ELT - Mosquera Pérez, Jhon Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2022)
English as a lingua franca is a phenomenon that has been gaining importance in the last few years. In the international scenario, scholarly literature has already explored the possible benefits of incorporating ELF in the ELT field. In Colombia, however, the empirical and conceptual studies on this area are scarce. Keeping this in mind, this reflective article discusses the possibility of progressively incorporating ELF in the Colombian ELT. In the first place, what ELF is, is analyzed, and this and other terms that have been used to refer to this linguistic phenomenon are differentiated. Second, some of the areas that need to take into consideration (materials design, assessment practices, to mention a few) are presented if we want to integrate ELF in Colombian ELT. Finally, some conclusions are presented, as well as potential research scenarios regarding ELF